Evidence from a Randomized Evaluation of the Household Welfare Impacts of Conditional and Unconditional Cash Transfers Given to Mothers or Fathers - Akresh, Richard (World Bank, Washington, DC, 2016)
This study conducted a randomized control trial in rural Burkina Faso to estimate the impact of alternative cash transfer delivery mechanisms on education, health, and household welfare outcomes. The two-year pilot program randomly distributed cash transfers that were either conditional or unconditional and were given to either mothers or fathers. Conditionality was linked to older children enrolling in school and attending regularly and younger children receiving preventive health check-ups. Compared with the control group, cash transfers improve children's education and health and household socioeconomic conditions. For school enrollment and most child health outcomes, conditional cash transfers outperform unconditional cash transfers. Giving cash to mothers does not lead to significantly better child health or education outcomes, and there is evidence that money given to fathers improves young children's health, particularly during years of poor rainfall. Cash transfers to fathers also yield relatively more household investment in livestock, cash crops, and improved housing.